Facial expressions in different communication settings: A case of whispering and speaking with a face mask in Farsi - Nasim Mahdinazhad Sardhaei; Marzena Żygis; Hamid Sharifzadeh (Language and Cognition)
This study addresses the importance of orofacial gestures and acoustic cues to execute prosodic patterns under different communicative settings in Farsi. Given that Farsi lacks morpho-syntactic markers for polar questions, we aim to determine whether specific facial movements accompany the prosodic correlates of questionhood in Farsi under conditions of degraded information, that is, whispering and wearing face masks. We hypothesise speakers will employ the most pronounced facial expressions when whispering questions with a face mask to compensate for the absence of F0, reduced intensity and lower face invisibility. To this end, we conducted an experiment with 10 Persian speakers producing 10 pairs of statements and questions in normal and whispered speech modes with and without face masks. Our results provide support to our hypotheses that speakers will intensify their orofacial expressions when confronted with marked conditions. We interpreted our results in terms of the ‘hand in hand’ and ‘trade-off’ hypothesis. In whispered speech, the parallel realisation of longer word duration and orofacial expressions may be a compensatory mechanism for the limited options to convey intonation. Also, the lower face coverage is mutually compensated for by word duration and intensified upper facial expressions, all of which in turn support the trade-off hypothesis.